Effectiveness of Nature- and Animal Assisted Mindfulness for Relapse Prevention in Depressed Patients With a History of Childhood Maltreatment - Schramm, Elisabeth; Breuninger, Christoph; Wohlfarth, Rainer; Elsaesser, Moritz; Piosczyk, Hannah; Fangmeier, Thomas (Frontiers in Psychiatry, 2022)
Background For relapse prevention in depression, conventional mindfulness programs such as the mindfulness-based cognitive therapy proved to be useful. However, early life trauma is a risk factor for having adverse experiences during meditation. Thus, for this patient group mindfulness skills are often difficult to learn and may be facilitated by using animals and a nature setting. Methods The aim of the study was to evaluate the preventative efficacy of a nature- and animal assisted mindfulness program (NAM) over the course of 1 year in unstable or partially remitted depressed patients with a history of early life trauma. NAM included 8 group sessions of 150 min each over 8 weeks plus one booster session. Sixty-seven participants were randomized to either NAM combined with treatment-as-usual (TAU; guideline oriented treatment) or TAU alone. The primary outcome was depression diagnosis over the course of 12 months after end of treatment. Secondary outcomes included clinician- and self-rated depressive symptoms, quality of life, mindfulness skills, and rumination post, and 12 months after the intervention. In addition, we evaluated the participants' satisfaction with the program. Results Analyses revealed significant differences in relapse rates and number of weeks depressed throughout the course in favor of NAM. Furthermore, global quality of life improved significantly more in the NAM group. There was no significant difference for other secondary outcomes. Satisfaction with the program was high with a low drop-out rate of 6%. The vast majority of the participants felt safe practicing mindfulness in nature and found sheep for assistance helpful and motivating. Conclusions A nature- and animal assisted mindfulness program proved to be feasible, highly acceptable, and more effective than standard treatment in preventing relapses in recurrently depressed patients with childhood maltreatment. Nature and animals can facilitate the engagement in the treatment process for individuals with a history of early trauma. However, further evidence in multicenter trials is necessary.